Preliminary data on the ostracod fauna from the Lower Toarcian of Peniche - Pinto, S. (2007)
Preliminary results of the systematic and biostratigraphical study of the ostracods from the Lower Toarcian (Polymorphum and Levisoni Zones) of Peniche are presented. Most of the identified species are recognized in other European countries. Biodiversity and species abundance are high in the first Zone, decreasing dramatically in the second one.